Enhanced spin–orbit coupling in tetragonally strained Fe–Co–B films. (7th June 2017) - Salikhov, R; Reichel, L; Zingsem, B; Abrudan, R; Edström, A; Thonig, D; Rusz, J; Eriksson, O; Schultz, L; Fähler, S; Farle, M; Wiedwald, U
Abstract: Tetragonally strained interstitial Fe–Co–B alloys were synthesized as epitaxial films grown on a 20 nm thick Au0.55 Cu0.45 buffer layer. Different ratios of the perpendicular to in-plane lattice constant c / a   =  1.013, 1.034 and 1.02 were stabilized by adding interstitial boron with different concentrations 0, 4, and 10 at.%, respectively. Using ferromagnetic resonance (FMR) and x-ray magnetic circular dichroism (XMCD) we found that the total orbital magnetic moment significantly increases with increasing c / a ratio, indicating that reduced crystal symmetry and interstitial B leads to a noticeable enhancement of the effect of spin–orbit coupling (SOC) in the Fe–Co–B alloys. First-principles calculations reveal that the increase in orbital magnetic moment mainly originates from B impurities in octahedral position and the reduced symmetry around B atoms. These findings offer the possibility to enhance SOC phenomena—namely the magnetocrystalline anisotropy and the orbital moment—by stabilizing anisotropic strain by doping 4 at.% B. Results on the influence of B doping on the Fe–Co film microstructure, their coercive field and magnetic relaxation are also presented.